Myostatin (MSTN) Gene Polymorphism Using PCR-RFLP Method In Kerinci Ducks - Shalsabila Novia Al-Sobri; Depison Depison; Eko Wiyanto (Universitas Bengkulu, 2022)
This study aims to determine body weight, body weight gain, and body measurements of male and female Kerinci ducks, as well as to determine the diversity of MSTN genes and the association of the MSTN gene on body weight, body weight gain, and body sizes in Kerinci ducks. The materials used were 96 Kerinci ducks and 96 Kerinci duck blood samples. Data analysis included: T-test, T2-hotelling, Principal Component Analysis (PCA), genotype frequency, allele, Hardy-Weinberg equilibrium, Heterozygosity, and PIC. The results showed that body weights at 2 and 3 months of age, body weight gain of 2-3 months and body sizes of 3 months old male Kerinci ducks were significantly different (P <0.05) higher than female Kerinci ducks. Body size markers of male and female Kerinci ducks were the length of the sternum, the length of the shank, and the circumference of the shank, while the shape identifier was the length of the wings. The MSTN|MboI gene in Kerinci ducks was polymorphic. The population of Kerinci ducks was in Hardy-Weinberg equilibrium (P<0.05). Kerinci duck population heterozygosity showed H0<He. The MSTN|MboI gene was associated with BB, PBB, and body measurements of male and female Kerinci ducks, and the best genotype was (-/-).